2016
DOI: 10.1002/app.43823
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of the impact strength of ethylene‐propylene random copolymers by nucleation

Abstract: Five ethylene-propylene random copolymers were nucleated with two soluble nucleating agents. Ethylene content changed between 1.7 and 5.3 wt%, while nucleating agent content was adjusted according to the solubility of the additive. It changed from 0 to 5000

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 47 publications
0
11
0
Order By: Relevance
“…Crystallization that does not take place in a quiescent melt, for example, in solution or under shear, is also affected by other phenomena. Wang et al showed that isothermal crystallization under shear flow may suppress the formation of γ phase, but more recent work by Horváth et al proves otherwise. De Rosa et al described the deformation behavior of iPPs with various content of stereodefects, showing that the γ form of an unstretched sample transforms to α form, and finally to mesomorphic phase at large strain …”
Section: Introductionmentioning
confidence: 99%
“…Crystallization that does not take place in a quiescent melt, for example, in solution or under shear, is also affected by other phenomena. Wang et al showed that isothermal crystallization under shear flow may suppress the formation of γ phase, but more recent work by Horváth et al proves otherwise. De Rosa et al described the deformation behavior of iPPs with various content of stereodefects, showing that the γ form of an unstretched sample transforms to α form, and finally to mesomorphic phase at large strain …”
Section: Introductionmentioning
confidence: 99%
“…Generally, the AFM results agree with deductions from PLOM analysis, which showed that the use of NA‐71 promoted the formation of a greater amount of crystalline phase that is smaller in size than the ones observed in samples nucleated with NX8000 and DMDBS. Moreover, it was possible to observe that neat i‐PP has larger‐sized spherulites compared to the crystalline structures (fibrillar and transcrystalline structures, similar to shish kebabs 8,10,21,22 ) formed in the samples containing the different nucleating agents.…”
Section: Resultsmentioning
confidence: 98%
“…It is well known that sorbitol derivatives, such as Millad, exhibit considerable potential as nucleating agents and additionally act as excellent clarifiers when incorporated (usually in small amounts) into a polyolefin matrix; thus, they are known to increase the nuclei density, leading to very small spherulites, so that the transparency is considerably improved [ 50 ]. Moreover, they enhance the γ modification in PPR copolymers [ 51 ].…”
Section: Resultsmentioning
confidence: 99%